Evaluation of protein C and S levels in patients with COVID-19 infection and their relation to disease severity - Ahmed Elshafie; Enas Foda; Mahmoud M. G. Yousef; Kareem A. Abd El-Naby (SpringerOpen, 2023)
Abstract Background The COVID-19 pandemic has been associated with millions of deaths around the world. One of the important causes of death associated with COVID-19 was pulmonary thromboembolism. The risk for venous thromboembolism was markedly increased in patients with COVID-19 especially those admitted to the intensive care unit. The aims of our study were to measure the protein C and S levels in COVID-19-infected patients in comparison with the normal population and to assess the correlation of protein C and S levels in the plasma to the severity of infection. Methods This was a case-control study measuring the protein C and S levels in patients infected with COVID-19 at the time of diagnosis compared to the normal population. The study included one hundred participants, sixty of them are patients with COVID-19, and forty of them are normal healthy adults. The patient group was subclassified into three subgroups according to disease severity: mild, moderate, and severe COVID-19 infections. Results The activity of protein C in the patient group serum was significantly lower than that in the control group serum (79.35 ± 26.017 vs 97.43 ± 15.007; p < 0.001). Protein S is also significantly decreased in patients' serum when compared to the control group (70.233 ± 22.476 vs 91 ± 14.498; p < 0.001). There was a statistically significant decrease in the levels of protein C and S associated with the increase in disease severity (p < 0.05). However, protein S showed no statistically significant difference between the moderate and severe disease subgroups. Conclusion The study concluded that the levels of protein C and S activities were both decreased in patients with COVID-19 when compared to the healthy population. It also concluded that the decrease in their levels is statistically significant in relation to the disease severity.